Haciendas in the Andean world, 16th-19th centuries. Historiographical essay: By knowing anyone do you know them all? - Luna, Pablo F. (2023)
The aim of this article is to recall the need for historical research on haciendas and the rural world in Central Andean America, which has been neglected int the last decades. At the same time, however, it review the questions that need to be addressed in order to go beyond the generalisations or conceptualisations that were made, especially during the second half of the 20th century. This historiographical approach try to concentrate on three main issues: firstly, the origins and formation of the Andean hacienda; secondly, the problem of work and remuneration in the rural world; thirdly, the form of possession represented by haciendas and latifundios and their evolution, in the face of the disentailment and the end of ecclesiastical and civil mortmain of the 19th century, before the agrarian reforms of the 20th century.